2018
DOI: 10.1128/iai.00673-17
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Protective Efficacy of Selected Immunodominant B-Cell Epitopes within Virulent Surface Proteins of Streptococcus pneumoniae

Abstract: Four previously identified immunodominant B-cell epitopes, located within known virulent pneumococcal proteins CbpD, PhtD, PhtE, and ZmpB, had shown promising immunological characteristics, indicating their potential to be used as vaccine antigens. In this study, we further evaluated the opsonophagocytic activity of antibodies against these epitopes and their capacity to protect mice from pneumococcal sepsis. An opsonophagocytic killing assay (OPKA) revealed that OPKA titers of human anti-peptide antibodies ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
0
6
0
Order By: Relevance
“…The impact of CbpD and CBPs in general on virulence is quite compelling, as it has been shown that the deletion of CbpD inhibits biofilm formation [ 74 ], while immunization with purified antibodies against a CbpD peptide fragment significantly increased survival of mice challenged intraperitoneally with lethal levels of a virulent serotype 3 pneumococcal strain [ 75 ]. Moreover, the addition of a mutated CSP1 peptide that inhibits the development of competence through outcompeting native CSP1, reduced CbpD and LytA expression levels and significantly decreased murine mortality after pneumococcal intranasal infection [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…The impact of CbpD and CBPs in general on virulence is quite compelling, as it has been shown that the deletion of CbpD inhibits biofilm formation [ 74 ], while immunization with purified antibodies against a CbpD peptide fragment significantly increased survival of mice challenged intraperitoneally with lethal levels of a virulent serotype 3 pneumococcal strain [ 75 ]. Moreover, the addition of a mutated CSP1 peptide that inhibits the development of competence through outcompeting native CSP1, reduced CbpD and LytA expression levels and significantly decreased murine mortality after pneumococcal intranasal infection [ 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chimeras of NTHi DNABII proteins were also immunogenic against NTHi biofilm in vitro ( 50 ). Likewise, a PD peptide was shown to elicit a superior immunogenic response compared to the whole PD protein ( 51 ). These mapping studies should also be performed for pneumococcal antigens to further understand vaccine potential and design.…”
Section: Discussionmentioning
confidence: 99%
“…A unique BamHI site separates the sequences encoding SUMO and His 6 in these plasmids. Plasmid pET28s-L 6 KD-SUMO-PhtD19 was used for the synthesis of the L 6 KD-SUMO-PhtD19 protein; this protein contains the PhtD19 peptide from pneumococcal histidine triad protein D (a.a. 200-219) (Papastamatiou et al, 2018) that is of interest as a vaccine component (Gorbunov et al, 2022).…”
Section: Plasmid Constructionmentioning
confidence: 99%